The effect of novel carbohydrate sources on nursery pig growth performance - Rantanen, M.M.; Cabrera, M.R.; Kim, I.H.; Burnham, L.L.; Hines, Robert H.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two growth assays were conducted to determine the effects of novel carbohydrate sources in Phase I and II starter diets on growth performance. In Exp. 1, 90 weanling pigs (avg initial body wt of 12.4 lb and 18 d of age) were used in a 38-d trial evaluating three carbohydrate sources: corn, tapioca, and rice flour. The carbohydrate sources were substituted for corn in diets formulated to 1.55 and 1.3% lysine for Phase I (d 0 to 10) and Phase II (d 10 to 24), respectively. All pigs were fed the same sorghum-soybean meal-based diet from d 24 to 38 post-weaning. For the overall experiment, pigs fed rice flour had greater average daily gain (ADG) compared with those fed tapioca, with those fed the diet containing corn having intermediate ADG. Pigs fed rice flour had improved feed to gain ratio (F/G) compared with those fed either corn or tapioca. In Exp. 2, 60 weanling pigs (avg initial body wt of 8.6 lb and 17 d of age) were used in a similar study to evaluate corn, ground sorghum, and roasted sorghum as the primary carbohydrate sources in Phase I and II diets. During d 0 to 10 post-weaning, pigs fed the corn diet had greater average daily feed intake (ADFI) than those fed the sorghum-based diets; however, no other differences in growth performance were observed during the experiment. These results suggest similar growth performance of starter pigs fed tapioca, sorghum, and roasted sorghum compared with those fed corn-based diets. However, pigs fed rice flour had improved F/G compared with those fed either corn or tapioca. Therefore, decisions on the use of novel carbohydrate sources in Phase I and II starter diets should be based on their price and availability relative to corn.
Keywords: Swine; Starter; Pigs; Tapioca; Sorghum; Rice; Roasting; Performance